Объяснение:
H2SO4 + Na2CO3 = Na2SO4 + CO2↑ + H2O
2H(+) + SO4(2-) + 2Na(+) + CO3(2-) = 2Na(+) + SO4(2-) + CO2↑ + H2O
2H(+) + CO3(2-) = CO2↑ + H2O
H2SO4 + 2KOH = K2SO4 + 2H2O
2H(+) + SO4(2-) + 2K(+) + 2OH(-) = 2K(+) + SO4(2-) + 2H2O
H(+) + OH(-) = H2O
H2SO4 + MgO = MgSO4 + H2O
2H(+) + SO4(2-) + MgO = Mg(2+) + SO4(2-) + H2O
2H(+) + MgO = Mg(2+) + H2O
H2SO4 + Fe = FeSO4 + H2
2H(+) +2e = H2(0) 1 в-ие
ок-ль
Fe(0) -2e = Fe(+2) 1 ок-ие
в-ль
H2SO4 + Zn(OH)2 = ZnSO4 + 2H2O
2H(+) + SO4(2-) + Zn(OH)2 = Zn(2+) + SO4(2-) + 2H2O
2H(+) + Zn(OH)2 = Zn(2+) + 2H2O
2NH₄⁺ + SO₄²⁻ + Ba²⁺ + 2Cl⁻ = BaSO₄↓ + 2NH₄⁺ + 2Cl⁻
Ba²⁺ + SO₄²⁻ = BaSO₄↓
NH₄Cl + AgNO₃ = AgCl↓ + NH₄NO₃
NH₄⁺ + Cl⁻ + Ag⁺ + NO₃⁻ = AgCl↓ + NH₄⁺ + NO₃⁻
Ag⁺ + Cl⁻ = AgCl↓